Combustion characteristics of extruded double base propellant based on ammonium perchlorate/aluminum binary mixture. (15th November 2017) - Elbasuney, Sherif; Fahd, Ahmed; Mostafa, Hosam E.
Abstract: Much attention has been directed toward the development of modified double base (MDB) propellant as it can offer high specific impulse as well as wide range of burning rate. One of the main approaches for the development of MDB propellant is the integration of potential oxidizers and metal fuels. This study reports on, the impact of potential oxidizers including potassium perchlorate (KP) and ammonium perchlorate (AP) on combustion characteristics of double base (DB) propellant. The impact of these energetic additives on burning rate and the characteristic exhaust velocity of gaseous product (C ∗ ) were evaluated using small-scale ballistic evaluation test motor. The two potential oxidizers KP and AP exhibited controversy effects; whereas KP positively impact the burning rate, AP positively impact C ∗ . The partial replacement of AP with aluminum metal fuel demonstrated a positive impact on both the burning rate and C ∗ . Aluminum metal fuel offered an increase the combustion temperature, and propellant thermal conductivity. Consequently, it could alter the combustion mechanism, by thinning the induction zone, allowing the luminous flame zone to be more adjacent to the burning surface. Accordingly, the combustion reaction could proceed faster. While, MDB based on AP/Al were found to be more energetic with an increase in calorific value to reference formulation using bomb calorimetery; they exhibited good thermal stability in terms of ignition temperature using cook off test, and accepted thermal behavior using DSC.